(untitled) (Nigerian Journal of Technology, 2018)
This paper is aimed at classifying three potential timbers grown in Nigeria using EN338 (2009) strength classification for structural size specimen. The timbers namely Vitex doniana, Ceiba pentandra and Pseudocedrela kotschyi were obtained in Ilorin, Kwara State of Nigeria. Physical and Mechanical properties of the selected timber species were determined in accordance with EN 13183-1 (2002) and EN 408 (2003) for structural timbers. Four point bending tests based on EN 408 (2003) with specimen 50x50x1000 mm were carried out using a Universal Testing Machine (UTM) to determine the bending strength and Modulus of Elasticity of the each timber specie. Characterisitc values of Bending strength, Modulus of Rupture and Density were determined using EN 384(2004). The timber species; Vitex doniana, Ceiba pentandra and Pseudocedrela kotschyi had equilibrium moisture content (EMC) of 15.70%, 13.71 % and 24.28 % respectively. Strength grading of timber species was then conducted by adjusting the material properties values of species to 12 % moisture content using the required adjustment factors. The timber were then graded according to EN338 (2009). Pseudocedrela kotschyi had the highest density of 813 kg/m3 followed by Vitex doniana (706 kg/m3) while Ceiba pentandra had the lowest density of 402 kg/m3. Vitex doniana, ceiba pentandra and Pseudocedrela kotschyi were assigned to strength class D30, C16 and D35 respectively in accordance with EN338(2004). http://dx.doi.org/10.4314/njt.v37i2.6